Promoting Exercise as a Therapeutic Intervention in Multiple Sclerosis: Barriers, Efficacy, and Social Prescribing Strategies - Mittl, Kristen; Agrawal, Devendra K. (Cardiology and Cardiovascular Medicine, 2026)
Multiple sclerosis (MS) is a chronic neurologic disease associated with significant physical, cognitive and social burden. Substantial evidence supports the safety and benefits of aerobic exercise for people with MS (pwMS), including improvements in fatigue, mobility, cognition, mood and quality of life. While exercise is recommended across all disability levels in clinical guidelines, real-world adherence remains low. This narrative review summarizes the benefits of aerobic exercise in MS and examines the symptom-related, psychosocial, socioeconomic, and healthcare system barriers that limits its implementation. These barriers reflect the broader influence of social determinants of health, which play a critical role in MS outcomes yet remain under-addressed in intervention research. We highlight social prescribing, a patient-centered approach that connects individuals to non-medical, community-based resources to address social needs, as a strategy to reduce barriers to exercise participation for pwMS. Future research should focus on developing and evaluating MS-specific interventions to improve exercise adherence and promote equitable access to physical activity to improve health outcomes.